Analisis Peran Petugas Lapangan Keluarga Berencana dalam Meningkatkan Jumlah Akseptor “MJKP” - Jusriani, Jusriani; Rifai , Muhammad; Juhanto , Asrijun (Politeknik Baubau, 2022)
Data from the Lasusua Health Center, Lasusua District, North Kolaka Regency in 2020 the number of couples of childbearing age who use contraception is 3321 people and those who use